The Effect of Smelting Temperature and Quantity of Flux on Aluminum Recovery Yield - Sumarsono, Randy Pratama; Anggono, Juliana; Risonarta, Victor (Mechanova, 2017)
Aluminum cans are widely used as food and beverage containers because of their properties. In practice, the consumption of canned drinks in the world and those recycled is not comparable. There are many challenges in recycling aluminum cans, one of which is the low yield of aluminum due to the formation of slag.From a literature study, it is known that the smelting temperature and the flux weight that added to the aluminium melt have an effect on the aluminum yield.Therefore in this research was conducted to smelt with 3 temperature variations were 720 oC, 740 oC and 760 oC and 3 flux weight variations were 0.5%; 0.75% and 1% based on weight of the aluminium can. The result show that experiment with melting temperature 760 oC and with weight flux of 1 % given highest recovery yield of 88.18% (388 grams).